PENERAPAN PENERAPAN METODE GDLC (Game Development Life Cycle) DALAM MEMBANGUN APLIKASI GAME EDUKASI PENGENALAN ALAT RUMAH UNTUK ANAK USIA DINI - April Zahmi; Aryadinata zaiyen, Muhammad (Ikatan Dosen Menulis, 2023)
Educational games are one of the effective educational media to increase children's knowledge in recognizing things around us such as household tools that will often be encountered, with the help of game applications it is hoped that they can help young children know the names of tools and their functions besides Educational games can also train children's cognitive and motor skills in learning something in a fun way to achieve the goal of creating a system methodology application that will be used, namely the Game Development Life Cycle (GDLC) approach. This method will be applied as a reference in building game applications. education according to the stages and steps in building the application to achieve a more interactive game.